The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1080/02724939992581
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia trachomatislower respiratory tract infection in infants

Abstract: Chlamydia trachomatis may be an important cause of lower respiratory tract infection (LRTI) in infants born to mothers amongst whom there is a high prevalence of sexually transmitted disease. A study of 100 ambulatory infants with signs of LRTI in South Africa showed that 6% had C. trachomatis infection. The majority of the infected infants had received chloramphenicol eye ointment as prophylaxis. Half had previously visited a health facility for the same illness but the infection has been misdiagnosed. Infant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
(4 reference statements)
0
7
0
Order By: Relevance
“…A study conducted in Alexandria and neighbouring rural areas in 2014 revealed the presence of C. pneumoniae in 31.4% of febrile children with respiratory infections using diagnostic real-time PCR [12] . Moreover, among 100 South African children with lower respiratory tract symptoms, 6% were reported to have C. trachomatis infections [13] .…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in Alexandria and neighbouring rural areas in 2014 revealed the presence of C. pneumoniae in 31.4% of febrile children with respiratory infections using diagnostic real-time PCR [12] . Moreover, among 100 South African children with lower respiratory tract symptoms, 6% were reported to have C. trachomatis infections [13] .…”
Section: Introductionmentioning
confidence: 99%
“…The "classical" presentation is the late onset type, which typically occurs around the sixth week of life. [33][34][35] The onset is an insidious development of nasal obstruction and/or discharge, tachypnea, and staccato cough, without fever or wheezing. Concomitant conjunctivitis is detected in half of the cases and serves as an important diagnostic clue to the diagnosis.…”
Section: Chlamydia Trachomatismentioning
confidence: 99%
“…Its etiological role in bronchopulmonary dysplasia in this group of patients has, however, not been ascertained yet. 35,36…”
Section: Chlamydia Trachomatismentioning
confidence: 99%
“…These may be the direct or indirect colonisation routes leading to the pharyngeal presence of C. trachomatis, which is the most frequent target site detected in about 70-77% of the infected neonates (Darville, 2005;Stenberg & Mårdh, 1990) and that serves as an infectious focus giving rise to recurrent conjunctivitis or pneumonia. Pharyngitis occasionally may persist up to 2 years of age or beyond (Bell et al, 1992;Mårdh, 2002;Rees et al, 1981, Zar et al, 1999. Fortunately, this type of colonisation remains often subclinical, as its progression to pneumonia is observed only in 30% of the cases (Chen et al, 2007).…”
Section: Respiratory Tract Infectionsmentioning
confidence: 99%
“…Severe congenital pneumonia due to C. trachomatis may even lead to fatal consequences in very preterm babies (25-32 weeks of gestation) (Attenburrow & Barker, 1986). Respiratory failure may affect primarily very preterm, low birth-weight infants, but there are documented cases of these also among near term babies or in untreated neonatal pneumonia (Herieka & Dhar, 2001, Zar et al, 1999. C. trachomatis infection has been associated with seriously chronic, occasionally lethal forms of pulmonary disorders of ventilated preterm neonates.…”
Section: Respiratory Tract Infectionsmentioning
confidence: 99%